Uncertainty and Monetary Policy in Good and Bad Times: A Replication of the VAR Investigation by Bloom (2009) - Giovanni Caggiano; Efrem Castelnuovo; Gabriela Nodari (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper revisits the well-known VAR evidence on the real effects of uncertainty shocks by Bloom (Econometrica 2009(3): 623-685. doi: 10.3982/ECTA6248). We replicate the results in a narrow sense using Eviews. In a wide sense, we extend his study by working with a smooth transition-VAR framework that allows for business cycle-dependent macroeconomic responses to an uncertainty shock. We find a significantly stronger response of real activity in recessions. Counterfactual simulations point to a greater effectiveness of systematic monetary policy in stabilizing real activity in expansions.
Keywords: C32; E32; 330; uncertainty shocks; nonlinear smooth transition Vector AutoRegressions; generalized impulse response functions; systematic monetary policy